Dampak Pemanfaatan Lahan Pekarangan Pada Kegiatan Kawasan Rumah Pangan Lestari (KRPL) Terhadap Peningkatan Pendapatan Rumah Tangga Di Kabupaten Asahan - Satria, Indra; Ginting, Rahmanta; Effendi, Ihsan (Universitas Medan Area, 2024)
The Impact of Yard Land Utilization on Sustainable Food House Area Activities (KRPL) on Increasing Household Income in Asahan Regency”. The purpose of this study was to analyze the household income of the social assistance beneficiary group before and after optimizing the use of yard land through the Sustainable Food House Area (KRPL) and to analyze the impact of home garden use on the Sustainable Food House Area (KRPL) activities on increasing household income of the beneficiary group in Tinggi Raja Village, Tinggi Raja District, Asahan Regency. This research uses a survey method. The method of determining the sample is determined randomly (random sampling) which makes the yard as a side income by the object of research. To test the difference in household income of the social assistance recipient group before and after the optimization of the use of yard land through the Sustainable Food House Area (KRPL), the t-test was used. Respondent's household income in Tinggi Raja Village, Tinggi Raja District, Asahan Regency before participating in KRPL was an average of Rp.1,500,000,-/month and after participating in KRPL an average of Rp.2,240,000,-/Month. KRPL activities have a positive impact on increasing the household income of respondents. The results of the t test obtained a t-count value of 9.448 with a sig (2-tailed) of 0.000 at a 95% confidence level (sig (2-tailed) = 0.000 0.05) concluded that there is a significant difference between the household income of respondents before and after participating in KRPL activities in Tinggi Raja Village, Tinggi Raja District, Asahan Regency.